2012
DOI: 10.1001/archoto.2012.1736
|View full text |Cite
|
Sign up to set email alerts
|

Categorizing Nasal Polyps by Severity and Controller Therapy

Abstract: Initial categorization of medication-naïve patients with CRSwNP and patients with established CRSwNP facilitated delivery of successful directed stepwise therapy that resulted in improvement of classification of severity in most patients. This proposed classification may provide a useful template for future studies comparing patients with CRSwNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In nasal polyps, the studies on symptom scores and endoscopic and radiologic scores (i.e., Lund-Mackay score) showed no correlation or poor correlation between diseases severity and symptoms 14 . Hopkins et al 13 reported that 21% of 1840 patients who underwent nasal surgery had Lund-Mackay scores similar to the asymptomatic patients.…”
Section: Discussionmentioning
confidence: 95%
“…In nasal polyps, the studies on symptom scores and endoscopic and radiologic scores (i.e., Lund-Mackay score) showed no correlation or poor correlation between diseases severity and symptoms 14 . Hopkins et al 13 reported that 21% of 1840 patients who underwent nasal surgery had Lund-Mackay scores similar to the asymptomatic patients.…”
Section: Discussionmentioning
confidence: 95%
“…Since then, many different CRS-specific QOL instruments have been developed and validated (16,17) . These include, but are not limited to, the Rhinosinusitis Disability Index (RSDI) (18) , Rhinosinusitis Quality of Life Survey (RhinoQOL) (19,20) , 16-item Sinonasal Outcome Test (21) , 20-item Sinonasal Outcome Test (22) , and Sinonasal Questionnaire (SNQ) (23,24) . At present the 22-item Sinonasal Outcome Test (SNOT-22) (25)(26)(27)(28) , which assesses the burden of CRS with a recall period of 2 weeks, is the most widely used and generally preferred CRS-specific QOL PROM (1,29,30) .…”
Section: Disease-specific Quality Of Lifementioning
confidence: 99%